2022
DOI: 10.1371/journal.pntd.0010726
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchis sinensis infection modulates key cytokines for essential immune response impacted by sex

Abstract: Infection with helminths can modulate the host immune response, which ultimately shape morbidity and mortality of the associated diseases. We studied key cytokines for essential immune response in sera from 229 southeastern China individuals infected with Clonorchis sinensis and 60 individuals without C. sinensis infection, and measured serum specific IgG and IgE against worms in these people. Individuals infected with C. sinensis had significantly higher antigen-specific IgG and IgE levels, which were positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…A study emphasized the potential risk of latent infection reactivation in individuals undergoing immunosuppressive anti-TNF treatment[ 12 ]. Additionally, another study supported a notable link between C. sinensis infection and immune suppression, influenced by gender dynamics[ 15 ]. Notably, AS patients with parasitic infection may undergo treatment using non-steroidal anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 97%
“…A study emphasized the potential risk of latent infection reactivation in individuals undergoing immunosuppressive anti-TNF treatment[ 12 ]. Additionally, another study supported a notable link between C. sinensis infection and immune suppression, influenced by gender dynamics[ 15 ]. Notably, AS patients with parasitic infection may undergo treatment using non-steroidal anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 97%
“…It was believed that the disparity in C . sinensis infection rates between sexes primarily stemmed from dietary habits, particularly the consumption of raw fish [ 33 ]. This behavior has contributed to a higher prevalence of C .…”
Section: Discussionmentioning
confidence: 99%
“…In alignment with Yuan Kuan Li et al's research on the correlation between C. sinensis infection and HCC [9], our results revealed that C. sinensis was highly related to HCC malignant behavior as exemplified by the BCLC stage and MVI. It was believed that the disparity in C. sinensis infection rates between sexes primarily stemmed from dietary habits, particularly the consumption of raw fish [33]. This behavior has contributed to a higher prevalence of C. sinensis infection among males compared to females [9,29].…”
Section: Sinensis Promotes Hcc By Activating Hcc Stemnessmentioning
confidence: 99%
“…C. sinensis adult worm antigen (CsAWA) was prepared as described previously ( Kan et al., 2022 ). In brief, C. sinensis adult worms suspended in PBS were lysed by sonication in an ice-chilled water bath.…”
Section: Methodsmentioning
confidence: 99%